KAJIAN ALELOKIMIA KULIT BUAH JENGKOL PADA GULMA PADI SAWAH - , Ir. Uswatun Nurjannah, MP.; , Prof. Dr. Ir. Prapto Yudono, MSc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Weeds is one of the major problems in increasing rice production. In Indonesia, there is a limited work has done on natural weed management by plant allelopathic potentiality, especially from jiringa hulls. Based on that, this research was carried out to : (1) identify the allelochemical compounds from fresh jiringa hulls